Analisis Implementasi Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik Pada Laporan Keuangan Umkm (Studi Kasus Pada Rumah Makan Apin Dan Smile Cell) - Rosmiati Rosmiati; Aminah Aminah; Khairudin Khairudin; Haninun Haninun; Sherly Wibowo (Jurnal Akuntansi dan Keuangan, 2018)
This research aimed to analyze the implementation of Financial Accounting Standards Entity Without Public Accountability on the financial statements of micro, small and medium enterprises.Based on the problems and aim of the research, this research uses qualitative research type. The data used in this research is secondary data in the form of financial statements of Apin restaurant and Smile Cell.The result of this research stated that Apin Restaurant and Smile Cell have not been able to implement Financial Accounting Standards of Entity Without Public Accountability in their financial report.